2018
DOI: 10.1016/j.chest.2018.04.039
|View full text |Cite
|
Sign up to set email alerts
|

α1-Antitrypsin Polymerizes in Alveolar Macrophages of Smokers With and Without α1-Antitrypsin Deficiency

Abstract: Polymerization of AAT in alveolar macrophages occurs in the lungs of individuals with AATD but also in smokers with normal AAT levels with or without COPD. Our findings highlight the similarities in the pathophysiology of COPD in individuals with and without AATD, adding a potentially important step to the mechanism of COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…Polymerized ZAAT plays a distinct pro-inflammatory role by acting as a strong neutrophil chemoattractant [83]. By applying a 2C1 monoclonal antibody, specific for polymerized AAT, ZAAT polymers have been detected in alveolar macrophages of individuals with AATD as well as in smokers with normal AAT levels with or without chronic obstructive lung disease (COPD) [84]. According to the latter observation, the similarities in the pathophysiology of COPD in individuals with or without AATD, could help in the understanding of the mechanism of COPD [84].…”
Section: Extrahepatic Manifestations Of Aatdmentioning
confidence: 99%
“…Polymerized ZAAT plays a distinct pro-inflammatory role by acting as a strong neutrophil chemoattractant [83]. By applying a 2C1 monoclonal antibody, specific for polymerized AAT, ZAAT polymers have been detected in alveolar macrophages of individuals with AATD as well as in smokers with normal AAT levels with or without chronic obstructive lung disease (COPD) [84]. According to the latter observation, the similarities in the pathophysiology of COPD in individuals with or without AATD, could help in the understanding of the mechanism of COPD [84].…”
Section: Extrahepatic Manifestations Of Aatdmentioning
confidence: 99%
“…However, a further study showed polymer accumulation did not occur in all PiZZ macrophages but only in 27% of cells observed in lung slices imaged by immunohistochemistry. 26 Interestingly, the authors also found AAT polymers in lung slices from non-deficient smokers with and without COPD, but not in non-smokers which may reflect the effect of oxidants on polymerisation even with normal AAT. The authors also showed that the percentage of alveolar macrophage containing AAT polymers correlated with pack year smoking history, FEV 1 /FVC ratio, small airways dysfunction, CD8 T cell and neutrophil numbers in the alveolar walls, suggesting that polymer accumulation could be important in both AATD and non-deficient COPD.…”
Section: Macrophages In Alpha-1 Antitrypsin Deficiencymentioning
confidence: 90%
“…22 Z-AAT polymers also co-localise with neutrophils in the lung tissue, which increases the local proteinase release thereby contributing to further interstitial damage, as previously reviewed. 23,24 Recently, AAT polymers have been identified in both monocytes 25 and macrophages 26 from AATD patients and evidence is building that these cells may also play a role in the development of AATD lung disease. The purpose of this review is to explore the potential implications of the local lung cells involved in non-liver AAT synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of AAT polymers in human alveolar macrophages, and their effects on lung inflammation, have recently been demonstrated [74] both in patients with COPD who have AAT-deficient PiZZ or PiZI variants and in smokers with PiMM who are otherwise healthy or have COPD.…”
Section: Polymers Of Aatmentioning
confidence: 99%